Effects of Exogenous Spermidine on Seed Germination and Physiological Metabolism of Rice Under NaCl Stress - Xiaohui Yang; Jian Xiong; Xiaole Du; Minmin Sun; Linchong Ding; Wanqi Mei; Zhiyuan Sun; Naijie Feng; Dianfeng Zheng; Xuefeng Shen (Plants)
Salt stress is one of the principal abiotic stresses limiting agricultural production and seriously inhibiting seed germination rates. This study selected the salt-tolerant rice variety HD961 and the salt-sensitive rice variety 9311 as experimental materials to investigate the physiological and metabolic effects of exogenous Spd seed priming on rice seeds and seedlings under NaCl stress. The experiment involved treating rice seeds with 0.1 mmol·L−1 Spd and then subjecting them to 100 mmol·L−1 NaCl stress for 24 h, with sampling for analysis at the 24 h and the four-leaf-one-heart stage. The results indicated that under NaCl stress, the rice’s germination and vigor indices significantly decreased. However, exogenous Spd seed priming reduced the accumulation of malondialdehyde, enhanced the capacity for osmotic adjustment, and increased the amylase and antioxidant activity by 50.07% and 26.26%, respectively. Under NaCl stress, the morphological development of rice seedlings was markedly inhibited, whereas exogenous Spd seed priming improved the aboveground and belowground biomass of the rice under stress conditions, as well as the content of photosynthetic pigments. It also reduced the damage to seedlings from electrical conductivity, helped maintain ionic balance, and promoted the excretion of Na+ and Cl− and the absorption of K+ and Ca2+. In the salt-sensitive rice variety 9311, the soluble protein content increased by 15.12% compared to the salt-tolerant rice variety HD961, especially under 100 mmol·L−1 NaCl stress, when the effect of exogenous Spd seed priming was more pronounced. In summary, these findings might provide new research perspectives and strategies for improving the salt tolerance of rice under NaCl stress.